Induction of variability in anthurium (Anthurium andreanum Lind.)through in vitro mutagenesis - Yashawant kumar srivastava (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2014)
Anthuriums (Anthuriumandreanum Lind.) of family Araceae, is highly valued for their exotic flowers and foliage. The attractivecharacteristics like vibrant inflorescence with straight spathe, candle-like spadix, exotic foliage and particularly the long lasting ‘flower’ of anthurium have ensured its great commercial importance. Anthurium is conventionally propagated by traditional vegetative methods such as stem cuttings and suckers which are tedious and not practical when carried out on a large scale. Plants derived from seeds showmarked variation in colour, quality, yield and time of first flowering. Seedviability and germination percentage are also low. Seed are viable only for two to three days and germination is as low as 20 to 30 per cent. Hence, there is a needto standardize a quicker method of propagation which may be achieved throughin vitro techniques.Tissue culture greatly increases the normal multiplication rate of plants and can provide a source of clean planting material. Vegetative means of propagation and poor seed viability limits genetic variation in anthurium and this necessitate alternate means to wider the genetic base. Invitromutation breeding is therefore being proposed as a means to create additional variation. The present study entitled “Induction of variability in anthurium (Anthurium andreanum Lind.)throughin vitro mutagenesis” was conducted with the objective to induce variation in anthurium var. Tropical and to characterise the variability through morphological and molecular assay. In vitro mutagenesis in anthurium was carried out using invitro cultures of var. Tropical as source material for treatments. Cultures were treated with gamma radiation as physical mutagen at different doses such as 5, 10, 15 and 20 Gy and chemical mutagen Ethyl Methane Sulphonate (EMS) at different concentrations such as 0.1, 0.2 and 0.5 per cent for 30 minutes. The irradiation was carried out at Radio Tracer Laboratory, College of Horticultureat room temperature using a gamma chamber equipped with 60Co source. After irradiation the cultures were kept in dark room for two days and later it was transferred to fresh media and incubated in light. The cultures were observed periodically for their response. Cultures exposed to higher doses lost their green appearance while the culture at lower doses (5 Gy) were good in multiplication and number of shoots compared to control. The cultures were sub cultured at one month interval; rooted plantlets planted out and hardened. The cultures differed in their in vitro response with respect to plant height, number of leaves, leaf dimensionsand flowering habit. Plantlets derived from low doses (5 Gy) of irradiation performed better than control while higher doses (15 to 20 Gy) gave stunted plants with more number of leaves. The cultures treated with EMS failed to regenerate except those with 0.1% treatment. Mutated plants started flowering within seven months and lot of variations were observed with respect to flower size, colour, length of flower stalk, arrangement of spathe and spadix. The selected variants were analysed at molecular level using RAPD and ISSR assay and genetic variation was confirmed. The desirable mutants are to be further evaluat